Language Errors in the Warta Kota Daily Newspaper - Endang Wiyanti; Yulian Dinihari; Heppy Atmapratiwi (Universitas Indraprasta PGRI, 2021)
Various features presented in the newspaper will add information to the reader. With increasing insight every day, they will increasingly be critical of the conditions that occur around found in writing in the newspaper. The language errors that occur are indicative of a lack of understanding of Bahasa. The researcher used a qualitative research approach with a type of descriptive study to be more focused and in accordance with the research objectives. The subject of this research is Warta Kota daily newspaper from October-December 2018 with the object of research being a mistake in various features of Warta Kota daily newspaper. Based on the data, errors analysis based on the largest to the smallest were Morphological errors (34.91%); Syntax error (16.04%); Error of Absorption Element (12.26); Word Writing errors (11.32%); Phonological errors (8.49%); Punctuation Writing Error (6.60%); Particle / Word Selection Writing errors and Word Combined Writing errors (3.77%); Front Word Writing errors (1.89%); and Error in the Use of Letters (0.94%).Keyword: Error Analysis, Newspaper